Proliferation of Media Content on TikTok and Its Impacts on Traditional Television Viewing Habits in Ghana - Gyasi, Edward; Abeka-Daniels, Marilyn; Owusu, Dennis Osei (Journal of Communication and Public Relations, 2025)
Premised on media substitution and uses and gratification theories, this study evaluates the increasing prominence of TikTok media content as it transforms traditional television viewing practices focusing on users between 18 and 34 years old. This research analyzed quantitative data to understand how short-form customized interactive TikTok content affects people's media habits and advertising results. User behavior has drastically evolved since people now dedicate their time primarily to TikTok rather than traditional television watching. Users transition to this platform primarily because it offers straightforward features and intelligent recommendation systems together with time-efficient content delivery. The research finds that TikTok continues to expand its influence on digital advertising landscapes. The research demonstrated that people chose TikTok ads over conventional television advertisements because they felt more connected and got better buying influences. Through its features of interactive content and user-generated material as well as viral trends TikTok functions effectively for advertisers by engaging audiences. According to the study conventional television networks need to find ways to innovate and integrate short-form digital content within their strategies for remaining relevant amid ongoing digital platform evolution. These findings suggest that the media world is transforming because viewers now interact with ads differently through TikTok and its associated apps as digital platforms take over consumer habits.